Mengoptimalkan Kepuasan Pelanggan melalui peran Digital Marketing, Brand Image, dan Segmentasi Pelanggan - Azhari, Azlan (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to analyze the role and influence of Digital Marketing, Brand Image, and Segmentation on Customer Satisfaction of Wardah cosmetic brand among Generation Z in Makassar City. The phenomenon of increasing consumption of cosmetic products among Gen Z and the shift in shopping behavior to the digital realm makes this topic relevant to study, especially in the context of local brand marketing strategies. This study uses a quantitative approach with an explanatory research type. The population in this study were all Generation Z women in Makassar City who had purchased Wardah products. The research sample was obtained through an accidental sampling technique of 100 respondents, according to the number of indicators multiplied by 5 based on the Hair et al. (2014) approach. Primary data were collected through an online questionnaire (Google Form) and measured using a 5-point Likert scale. The data analysis technique used was multiple linear regression, with the help of SPSS version 22, and equipped with validity, reliability, t-test, F-test, and coefficient of determination (R²) tests. The results of the study showed that partially and simultaneously, the three independent variables (Digital Marketing, Brand Image, and Segmentation) had a significant effect on Customer Satisfaction. Among the three, Segmentation is the most dominant variable with the highest regression coefficient value (0.400). This indicates that the right segmentation strategy based on the needs, lifestyle, and specific characteristics of Gen Z has the greatest impact on increasing customer satisfaction with the Wardah brand.